The application of Gene Function Markers for identification of high quality of Vietnamese traditional rice varieties - Ky Huynh; Manh Nguyen Van; An Tinh Pham; Nguyen Pham; Nhu Dien Huynh; Thanh Le (CTU Journal of Innovation and Sustainable Development)
In today's growing economy, consumer demand for rice is evolving, with a preference for high-quality varieties that are soft and aromatic when cooked. We conducted a study to identify high-quality rice varieties that meet these consumer preferences. Molecular markers were used to find genes linked to desirable traits in rice. These genes are DRR-GL for grain length (gene GS3), Wxin1 for amylose content (gene Wx), and BADH2 for aroma. The findings revealed that the molecular marker DRR-GL, used with primers EFP, IRSP, ERP, and IFLP, accounted for 90% of the expression of the long-grain phenotype. Similarly, the Wxin1 marker, with primers GF, TR, GR, and TF, explained 90% of the variation in amylose content. The BADH2 marker, using primers ESP and IFAP, INSP, and EAP, accounted for 100% of the aroma phenotype expression across all tested varieties. Among the 20 traditional rice varieties examined, the variety Nep Trong Vo exhibited superior qualities, including an elongated grain length of 7.13 mm, an average amylose content of 17.58%, a soft gel consistency graded at 3, and high heat resistance also graded at 3. These characteristics make Nep Trong Vo a promising candidate for meeting the high-quality standards demanded by consumers.